Studi Numerik Kontur Pola Aliran Fluida Pendinginan Pada Mold Injeksi Molding - Angger Bagus Prasetiyo; Fauzun Fauzun; Azhim Asyratul Azmi; Rizqi Ilmal Yaqin (P3M Politeknik Negeri Cilacap, 2021)
The conventional cooling process was chosen because of the better estimation of manufacturing times and lower manufacturing costs. One alternative to minimize the decline in quality in plastic products is by using a conformal cooling process. This study will compare the contours of the fluid flow pattern between conventional cooling channels and conformal cooling channels. Case study on a box-shaped product made of PP material which has a melt temperature of 205 ° C. 3D product images were made with Solidwork 2017 software and process simulation using fluent 19.0 software. The results showed that the temperature flow pattern in the conformal channel resulted in a temperature absorption of around 303.2K while the conventional cooling channel was around 302.5K. Then the coolant channel that experiences high pressure drop occurs in the conformal cooling channel around 88888.9 pascals and the conventional cooling channel around 355555.6 pascals.